Healthy Eating: Approaching the Selection, Preparation, and Consumption of Healthy Food as Choice Behavior - Rafacz, Sharlet D. (Perspect Behav Sci, 2019)
Healthy eating has important well-being and financial implications for our society. As such, it is critical that the field of behavior science and behavior analysis conduct more research in this area so that effective interventions may be developed. One barrier to addressing healthy eating may be conceptual. Far from being a single response, eating is comprised of a series of choice responses. These selection, preparation and consumption responses form a temporally delayed behavioral chain. When designing interventions to address healthy eating, therefore, one must not only consider the specific target response, but alternative response options, and the effect of changing one response on other choices in the chain. The purpose of this article is to refine the analysis of healthy eating behavior, provide examples of research conducted in this area, and discuss how these interventions may influence this chain of responses. It is hoped that by doing so, additional research will be conducted and disseminated so that individuals, organizations, and policy makers can implement more effective interventions for healthy eating.